Effect of an interprofessional collaboration intervention on doctor–nurse collaboration in community health centers: A quasi-experimental study - Yuliana, Yuliana; Aulia, Siti (Journal of Community Nursing and Primary Care, 2025)
Background: Interprofessional collaboration is a key component of effective primary healthcare delivery because coordinated teamwork among health professionals supports communication, continuity of care, and service integration. However, structured intervention studies examining doctor–nurse collaboration in community health centers remain limited, particularly in routine primary care settings. Objective: This study aimed to examine the effect of an interprofessional collaboration intervention on doctor–nurse collaboration in community health centers. Methods: A quasi-experimental pretest–posttest study with a control group was conducted among 70 respondents, comprising 35 participants in the intervention group and 35 participants in the control group. Participants were doctors and nurses working in community health centers and directly involved in collaborative patient care. Collaboration was measured using the Collaborative Practice Assessment Tool (CPAT). Baseline data were collected before the intervention, followed by posttest assessment after the intervention period. Descriptive statistics were used to summarize respondent characteristics, while within-group and between-group comparisons were performed to assess changes in total collaboration scores. Effect size was calculated using Cohen’s d. Results: The intervention and control groups had comparable baseline collaboration scores before the intervention. The intervention group showed a marked increase in the mean total collaboration score from 72.8 ± 9.8 at pretest to 80.0 ± 10.0 at posttest, whereas the control group showed a smaller increase from 72.1 ± 10.1 to 73.9 ± 10.0. The posttest mean difference between groups was 6.1 points, indicating better collaboration outcomes in the intervention group. The intervention produced a moderate effect size (Cohen’s d = 0.61), suggesting a meaningful practical effect on doctor–nurse collaboration in community health centers. Conclusion: The interprofessional collaboration intervention was effective in improving doctor–nurse collaboration in community health centers. Structured collaborative strategies may strengthen teamwork in primary care and support better service delivery in routine practice.